Penerapan Strategi The Power of Two dalam Pembelajaran Fikih untuk Meningkatkan Kemampuan Berpikir Siswa Madrasah Ibtidaiyah - Nur Rosyidah Rahmawati (Jurnal Budi Pekerti Agama Islam, 2023)
This study aims to determine the effect of the use of the Power of Two cooperative learning model on students' thinking skills in the Fikih material at MI Nurul Yaqin Donoyudan. This study uses a qualitative approach with a descriptive method that refers to literature observations, observations, and documentation. The Power of Two model is applied by forming small groups of two students who discuss the material being studied before sharing their understanding with other groups. This strategy is designed to encourage active interaction, increase self-confidence, and deepen understanding of the material. During the learning process, researchers observed an increase in collaboration between students and their ability to express opinions and understand Fikih concepts. The results of the study indicate that the application of this model can improve students' thinking skills, both in cognitive and affective aspects, which are marked by an increase in the quality of discussions, understanding of concepts, and active participation in learning activities.